Phytochemical Contents of Torbangun (Coleus amboinicus Lour) from Fractionation of Pressurized Liquid Extraction - Farida Laila; Dedi Fardiaz; Nancy Dewi Yuliana; Muhammad Rizal Martua Damanik; Fitriya Nur Anissa Dewi (Jurnal Ilmu Pertanian Indonesia, 2020)
Coleus amboinicus (Lour) (torbangun) has been used traditionally as a breast milk stimulant, flavoring agent in many cuisines, and reported to possess many pharmacological values. The aim of this study was to explore the utility of the Pressurized Liquid Extraction (PLE) technique to identify the phytochemical contents of torbangun. In this study, total phenolic content and flavonoid in torbangun were determined using spectrophotometric method. The GC-MS analysis was used to identify the chemical constituents of torbangun, which was sequentially extracted with a wide range of solvent or solvent mixture from nonpolar-moderately polar and finally polar solvent. Total phenolic and flavonoid contents in the methanol extract of torbangun were 42.17±2.96 mg GAE/g and 11.20±0.58 mg QE/g, respectively. The identified chemical constituents in torbangun were sugar, hydrocarbon, ketone, terpenes, phenolics, fatty acid, fatty alcohol, steroids, alkaloids, and others, whereas the dominant constituents were phenolic compound, alkane, and sugar. In conclusion, this study demonstrated the effectiveness and rapid extraction of the PLE technique. Many valuable compounds in torbangun were extracted using gradual composition of solvent and were able to identify certain compounds in different polarities of solvents that are important in functional food preparation, pharmaceutical, and metabolomics research. Keywords: bioactive, extract, nontoxic, plant, solvent